Perlindungan Hukum terhadap Eksploitasi Anak di Bawah Umur oleh Orang Tua di Kota Manado: Studi pada Dinas Pemberdayaan Perempuan dan Perlindungan Anak - Olly Frida Adolf Wilem Kalalo; Ritania Regina Jacobus (Eksekusi : Jurnal Ilmu Hukum dan Administrasi Negara, 2026)
Economic exploitation of children remains a serious issue within the child protection system in Indonesia, particularly in urban areas experiencing high socio-economic pressure. This study aims to analyze the forms of legal protection provided to children who become victims of economic exploitation by their parents in Manado City and to identify the factors that cause children to become involved in street-based economic activities. The research employed an empirical legal method with a socio-juridical approach. Data were collected through semi-structured interviews, documentation, library research, and case-handling records from the Office of Women’s Empowerment and Child Protection of Manado City. The data were analyzed using a qualitative descriptive method to understand the relationship between child protection legal norms and social practices within society. The findings reveal that legal protection has been implemented through preventive and repressive measures, including public outreach, legal education, psychological assistance, social rehabilitation, and inter-agency coordination. However, its implementation has not yet been optimal due to family poverty, low parental education, weak legal awareness, permissive social environments, and limited institutional capacity at the regional level. This study emphasizes that protecting children from economic exploitation requires stronger law enforcement, social protection for vulnerable families, community economic empowerment, and an integrated child protection system to ensure children’s rights to education, welfare, and development are sustainably protected.